The influence of TiO2 and SiO2 nanoparticles on filtration properties of drilling muds (Rudarsko-geološko-naftni zbornik, 2019)
During the drilling of a well, differential pressure causes filtration of the mud liquid phase into the surrounding rocks. To reduce the filtrate invasion in the rock, it is necessary to maintain the density of the mud. Also, Wellbore Strengthen- ing Materials (WSM) can be preventively added to the mud to increase the fracture initiation pressure of the drilled formation. The solid particles from the mud create a mud cake on the wellbore wall, which, for conventional drilling, implies the use of bentonite and barite whose particle dimensions range from 0.1 to 100 μm. While drilling shales, rocks which contain pores that have an average pore size of 10 to 30 nm, it is not possible to create a high-quality mud cake, so water passes into the shale and creates wellbore instability problems. To stabilize the shale, the petroleum industry uses oil-based muds, but due to their environmental impact, it is not always possible to implement them. Nanoparticles, because of their small dimensions, can enter into the nanopores and fill this space and strengthen the rock, resulting in decreased filtration. In this paper, a review of previous laboratory research of adding nanoparticles on filtration is shown. Also, the impact of adding nanoparticles on API and HTHP filtration is examined by adding TiO2 and SiO2 nanoparticles in concentrations of 0.5 wt% and 1 wt% to the five water-based muds. The best result was obtained with TiO2 nanoparti- cles at a concentration of 0.5 wt%.